DISCOURSE ANALYSIS ON DAM AND ITS ASPECT OF ECOLOGICAL AND SOCIAL UNFRIENDLINESS IN EDWARD ABBEY’S THE MONKEY WRENCH GANG - Syarifah, Saniyatus; Tirmidi, Tirmidi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the main themes and perceptions of dams as unsustainable development in Edward Abbey's The Monkey Wrench Gang. Using qualitative discourse analysis, this research applies Kristeva’s conceptual framework dividing analysis into suprasegmental and intertextual dimensions. Suprasegmental analysis employs Mandler-Johnson's story grammar approach, while intertextual analysis applies Gee’s technique with McCully’s theoretical framework on large dam ecology and politics. Results reveal the novel's central theme as radical resistance to environmental damage from sustainability-ignoring development. Four environmental activists' transformation from peaceful advocacy to sabotage illustrates disappointment with institutional indifference. Intertextual analysis shows dams perceived as unsustainable development through two dimensions. The ecological dimension includes hydrological cycle disruptions, habitat fragmentation, and sedimentation problems. The social dimension encompasses forced displacement of indigenous peoples, unequal benefit distribution, and traditional livelihood destruction. This research contributes to literature-based language teaching methodology by integrating ecological awareness. Findings demonstrate consistent dam criticism across scientific and literary perspectives, viewing dams as development sacrificing long-term sustainability for short-term gains. Further research should explore other ecological literary works with similar approaches to strengthen the ecoliterature corpus and develop literature-based curriculum models integrating environmental awareness in English foreign language teaching.